Pendekatan Hadis dalam Penafsiran Al-Qur'an : Mendedah Metode Al-Bukhārī dalam Kitab Shaḥīḥ Al-Bukhārī - Muhammad Alamudin; Ahmad Nurhamdani; Iqbal Nursyahbani; Fahmi Husen; Syafi’i, Ahmad Musta’in (Moderasi : Journal of Islamic Studies, 2025)
The interpretation of the Qur'an remains a controversial issue among Muslims. The various methods of interpretation employed by scholars have led to differing opinions regarding the meanings and implications of Qur'anic verses. In this context, the hadith approach as a primary source for interpreting the Qur'an becomes crucial. Al-Bukhārī, as one of the prominent hadith scholars, possesses a unique method of using hadith as a source for Qur'anic interpretation. This research aims to analyze Al-Bukhārī's method in utilizing hadith as a source for interpreting the Qur'an and its implications for understanding the Qur'an. By employing a qualitative research method, this study analyzes the book of Ṣaḥīḥ Al-Bukhārī as a primary data source. The findings indicate that Al-Bukhārī uses hadith as a source for interpreting the Qur'an to clarify the meanings of its verses and to establish Islamic laws. The implications of this research suggest that the hadith approach in interpreting the Qur'an can aid in clarifying its meanings and establishing more accurate legal rulings.